Searching for the perfect goalkeeping personality. Myth or reality? - Spielmann, J.; Otte, F.; Schumacher, T.; Mayer, J.; Klatt, S. (Frontiers in Psychology, 2024)
Background: Psychological factors such as personality characteristics are influential factors of the goalkeeping performance in football (soccer). Not only for individualized treatment in practice, also from a scientific point of view, profiling goalkeepers is a relevant part of understanding athletes. The aim of this study was to investigate personality traits of goalkeepers of different expertise, age, and sex.